2018 Southeast Lachlan Seismic Survey: New Heights. Issue 1 (1st December 2019) - Costelloe, Ross; Fomin, Tanya; Cayley, Ross; Cairns, Cameron; Rawling, Tim
Summary: Six hundred and twenty nine kilometres of deep crustal reflection data were collected for the Southeast Lachlan 2D seismic survey during March to April 2018. The purpose of the survey was to image the Lachlan Orogen geology, as a key to the geodynamic evolution and mineral potential of Victoria and New South Wales with implications for eastern Australia as well as natural hazard mapping. The project is a collaboration between Geoscience Australia, the Geological Survey of Victoria, the Geological Survey of New South Wales, and AuScope Ltd. The seismic data were collected by Terrex Seismic and processed by Downunder Geosolutions, and posed significant challenges in both phases. The project has been successful in obtaining final images of the whole crust in this area of the Lachlan Orogen and fundamental structural information on the crustal architecture in southeast Australia.